2021
DOI: 10.2196/29390
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of Weight Loss Surgery in Instagram Posts: Successive Sampling Study

Abstract: Background The majority of American adults search for health and illness information on the internet. However, the quality and accuracy of this information are notoriously variable. With the advent of social media, US individuals have increasingly shared their own health and illness experiences, including those related to bariatric surgery, on social media platforms. Previous research has found that peer-to-peer requesting and giving of advice related to bariatric surgery on social media is common,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It seems very likely that this paradigm shift was enabled by a combination of commitment from healthcare providers [26,27], maturing telehealth technologies and the related governing regulations [28], and patient engagement with the dedicated platforms. Thus far, several reports based on online questionnaires have shown that bariatric patients were familiar with using the Internet [29,30] to search for bariatric-related information, with 95.1% of bariatric patients having a connection [31]. Not surprisingly, 80 of the 87 patients (91.9%) in our study population agreed to a first bariatric TC, with only 27.5% of the patients reporting limited web connectivity.…”
Section: Discussionmentioning
confidence: 63%
“…It seems very likely that this paradigm shift was enabled by a combination of commitment from healthcare providers [26,27], maturing telehealth technologies and the related governing regulations [28], and patient engagement with the dedicated platforms. Thus far, several reports based on online questionnaires have shown that bariatric patients were familiar with using the Internet [29,30] to search for bariatric-related information, with 95.1% of bariatric patients having a connection [31]. Not surprisingly, 80 of the 87 patients (91.9%) in our study population agreed to a first bariatric TC, with only 27.5% of the patients reporting limited web connectivity.…”
Section: Discussionmentioning
confidence: 63%
“…We focused on general and publicly accessed sites as well as health-related forums. The results from other studies using other media sources such as Facebook and Instagram demonstrated that giving and seeking recommendations, sharing nutrition-related advice, discussing post-bariatric changes, and sharing experiences after surgery are the most common topics ( 13 , 29 , 30 ). In a previous study, a research group used free word association network analysis to examine the mental and emotional representation of weight loss in bariatric surgery patients on Facebook ( 31 ).…”
Section: Discussionmentioning
confidence: 97%
“…Social media serves as a repository for users to access and exchange information and to provide and receive support from those with similar experiences 22 . These sites provide the safety of anonymity, which may be one reason why people living with high levels of stigma, including those with obesity, are avid users when seeking health information 57 …”
Section: Methodsmentioning
confidence: 99%
“…22 These sites provide the safety of anonymity, which may be one reason why people living with high levels of stigma, including those with obesity, are avid users when seeking health information. 57 A recent (Robinson et al 46 ) narrative review concluded that online forums, including social media, offered people going through bariatric surgery a place to seek quick, relatable and supportive advice from others with lived experience, which assisted in decision making. 46 People, especially those long-term post-surgery, look for encouragement and inspiration from social media, less so education.…”
Section: Appsmentioning
confidence: 99%